The influence of leadership, motivation, discipline, and work experience on the performance of healthcare workers at the Wuna Public Health Center - Sri Rahayuningsi Apu; Irma Irma; Agnes Mersatika Hartoyo (PT WIM Solusi Prima, 2026)
Healthcare worker shortages represent a serious global issue. In Indonesia, the provision of healthcare services in underdeveloped, remote, and border areas remains suboptimal, ultimately affecting the performance achievements of primary care. This study aims to determine the relationship between leadership, motivation, work discipline, and work experience with the performance of healthcare workers. This was a quantitative study with a cross-sectional approach, conducted at the Wuna Public Health Center, Barangka District, West Muna Regency, Southeast Sulawesi Province, in 2025. The study sample consisted of 53 healthcare workers selected using a total sampling technique. Bivariate data analysis was performed using the Chi-Square test. The results showed a significant relationship between leadership (p = 0.041), work discipline (p = 0.000), and work experience (p = 0.023) with the performance of healthcare workers. However, the motivation variable did not show a significant relationship (p = 0.500) with performance. In conclusion, leadership, work discipline, and work experience are critical determinants of healthcare worker performance at the Wuna Public Health Center, whereas motivation has no direct correlation. The public health center management is recommended to maintain strict discipline and facilitate regular training programs to support the competence enhancement of healthcare workers with minimal work experience.